Impact of a Home Hospice Visit Program on Third-Year Medical Students: A qualitative analysis of student reflections. Issue 1 (March 2015) - Strano-Paul, Lisa; Lane, Susan; Lu, Wei-Hsin; Chandran, Latha
Aim: This study evaluates the impact of an interprofessional home hospice visit (HHV) on third-year medical students' attitudes toward, and understanding of, end-of-life care and the visit's effect on students' views of their emerging professional roles and identities. Methods: All third-year medical students at Stony Brook School of Medicine in Stony Brook, New York, USA, participated in an HHV. A didactic session preceded the HHV. Subsequently, students were required to submit a piece of reflective writing detailing the impact of the visit. We conducted a qualitative analysis of a random sample drawn from the 467 submitted reflections. Results: Six themes emerged from the student reflections: three were related to the students' direct observations during the HHV, and three were related to the reflective learning of the students based on their HHV experience. Conclusion: The qualitative analysis of the reflective writings showed that the students gained a deep appreciation of the human identity of hospice patients and a humanistic understanding of their own role as future physicians.